Evaluating and Optimizing a Protocol for Mesodermal Differentiation of Pluripotent Stem Cells towards Cardiomyocytes and Adipocytes - Lundin, Anders (My University, 2013)
The fat epidemic is an increasing issue in today’s society, and with it follows obesity-related diseases, such as type 2 diabetes and coronary heart disease. Many of today’s drug candidates are withdrawn from the market due to negative cardiac effect, which result in huge setbacks for drug companies if detected at late stage trials Therefore, there is a necessity of appropriate in vitro models, which can detect these toxic effects at early stages in drug development. Consequently, there is an increasing demand in providing cells with high biological relevance. A large portion of the study models used today are performed with in vitro cells lines of cancerous origin, and often from species other than human. In addition, usage of different in vivo models also add to the complexity with the matter of accurate translability. This issue can be addressed by using primary cells. However, this raises the problem of accessibility, which can almost be impracticable when it comes to accessing and isolating cells from neuronal or heart tissue. Fatty tissue is more accessible, but the amount of cells that can be isolated from a subject are not sufficient to run large drug screens. Using cells from different subjects can be a solution to the problem of poor accessibility, but creates a large complexity of donor to donor variations. Another model, using pluripotent stem cells (PSC), provides beneficial properties of indefinite growth with sustained pluripotency, an immense source of cells, and the theoretical possibility of differentiation into any cell type in the body. In addition, the cells can be of human origin, providing a good biological relevance. The discovery and development of the induced pluripotent stem cell (iPSC) technique, meaning the possibility of creating a PSC from a somatic cell, also circumvented the major ethical hurdles of isolating embryonic stem cells. To be able to take advantage of the beneficial properties of the iPSC technology there is a need for establishing robust differentiation protocols, which can transform iPSCs into mature functional somatic cells. This thesis focused on evaluating and optimizing differentiation protocols to derived cardiomyocytes and adipocytes from iPSCs. A robust protocol for providing stem cell derived adipocytes was not achieved. Evaluation of the differentiation process mainly focused on functional assays, such as; glucose uptake of radioactive isotopes, lipolysis and western blot. These assays did not supply data supporting derivation of functional adipocytes. The observed poor functionality was due to the low percentage of derived adipocytes, a feature correlating with recent publications. Differentiation of cardiomyocytes was achieved, both through embryo body formation and by direct differentiation in a monolayer format. Characterization of the cardiomyocytes was conducted by immunocytochemistry (ICC), fluorescent activated cell sorting (FACS), quantitative PCR and high content imaging (ImageXpress). Moreover, the cardiomyocytes exhibited the characteristics of spontaneous contractions and expressed the typical cardiac markers, as Nkx2.5 and cTnT. Finally, the outcome of the cardiomyocyte differentiation protocol show promising results for future application and development as an in vitro model for drug screening.
Keywords: Energi; Livsvetenskaper; Materialvetenskap; Grundläggande vetenskaper; Hållbar utveckling; Innovation och entreprenörskap (nyttiggörande); Biologiska vetenskaper; Energy; Life Science; Materials Science; Basic Sciences; Sustainable Development; Innovation & Entrepreneurship; Biological Sciences